Teknik Penyembunyian Data Menggunakan Kombinasi Kriptografi Rijndael dan Steganografi Least Significant Bit (LSB) - Dwi Ely Kurniawan; Narupi Narupi (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
In this study, techniques for Data Hiding performed by combining the Rijndael algorithm and the Least Significant Bit (LSB). At first the sender encrypts the message and inserts the message into the image, and then decipher the hidden message back that can be read by the recipient. System testing is done by sending data from Rijndael encryption and Least Significant Bits to the various media sender. Results from the study indicate that the data is encrypted before and after have the same relative size, but changing the amount of image quality depends on the bit value of the quality of media and messages. The more difference bit value, the greater the changes.